Allergen‐specific Th2 responses in young children precede sensitization later in life. Issue 3 (28th January 2014) - Reubsaet, L. L.; Meerding, J.; Scholman, R.; Arets, B.; Prakken, B. J.; van, F.; Knol, E. F.
Abstract Allergic sensitization is initiated by allergen‐specific Th2‐cell responses. Data on early allergen‐specific T‐cell responses in allergic children are scarce. We hypothesized that allergen‐specific Th2‐cell responses can be detected preceding sensitization. Therefore, peripheral blood mononuclear cells (PBMC) of nonsensitized, 'not‐yet' sensitized or sensitized children were cultured with highly purified allergens. Cytokine levels in supernatant were determined using multiplex assay and GATA3 expression by flow cytometry. PBMC of sensitized children aged 3 and 5 years showed higher production of IL4, IL5 and IL13 and higher expression of GATA3 in response to purified allergens compared to nonsensitized children. PBMC of children that were 'not‐yet' sensitized already showed higher levels of IL5 and IL13 and higher GATA3 expression at age 3 years. This shows that allergen‐specific in vitro Th2 responses precede the detection of allergen‐specific IgE, which can provide a window of opportunity for novel therapeutic interventions.